HUKUK YARGILAMASI YÖNÜNDEN ZAMANAŞIMI - (:unkn) unknown (My University, 2016)
Geçmişi erken dönem Roma Hukuku'na dayanan zamanaşımı müessesi Türk borçlar hukukuna göre bir maddi hukuk kurumudur ve hukuk yargılaması yönünden bir def'idir. Def'i, davalının esasında borçlu olduğu bir edimi özel bir nedene dayanarak yerine getirmekten kaçınma imkânı veren bir haktır. Bu açıdan zamanaşımı borcun dava edilebilirliğini ortadan kaldırmaktadır ve nitekim zamanaşımına uğramış bu borç eksik borç olmaktadır. Ayrıca, zamanaşımı def'i maddi hukukun yanı sıra hukuk yargılaması yönünden de önem arz etmektedir. Zamanaşımı def'inin hukuk yargılamasında ileri sürülme zaman ve koşulları birtakım özellikler taşımaktadır. Bu çalışmamızda, zamanaşımı kavramının hukuk yargılaması yönünden değerlendirilmesi inceleme konusu yapılacaktır.

According to Turkish Obligation Law, statue of limitation which date back to early Roman Law is a establishment of substantive law and plea in terms of legal proceeding. In fact the plea is a right to bring avoidance to the defendant of an act of the debtor on the basis of a special cause. From this point of view the statute of limitation abrogation availability lawsuit of debt and in this way this debt is getting which barred by prescription is imperfect obligation. Also plea of statue of limitation is in substantive law as well as important in terms of legal proceedings. Making of plea of statue limitation has different features about time and conditions in legal proceeding. In our study, the concept statute of limitations's the investigation in terms of legal proceedings will be a research subject.
STATUTE OF LIMITATION IN TERMS OF LEGAL PROCEEDINGS
Keywords: Hukuk